PSYCHOLOGICAL FACTORS THAT INFLUENCE COMPLIANCE WITH TRAFFIC RULES AMONG ADOLESCENT MOTORCYCLISTS - Julian Amriwijaya; Sunggoro Trirahardjo (Adisam Publisher, 2026)
Psychological factors play an important role in traffic compliance. Some psychological aspects that can influence driver behavior include self-safety motivation, self-control, and legal awareness. In psychology, the problem of compliance with the law alone is indeed less effective in implementing the law in society. Returning to the definition above, compliance is limited to only not violating the rules or avoiding punishment, so the attitude of compliance is only temporary. It would be ideal if traffic regulations were not only obeyed but also not internalized. If people have internalized the rules, they will obey them very much at all times. Because if they violate what has been internalized, then conflict will arise within themselves, in general people try to avoid conflicts. The relationship between psychological factors and compliance with traffic regulations is very complex and is influenced by various elements, including individual motivation, self-control, and legal awareness. Efforts to improve compliance must consider these aspects to create a safer traffic environment. Adolescent compliance with traffic regulations, especially for motorcyclists, is influenced by various psychological factors. Overall, these psychological factors interact with each other and influence adolescent behavior in traffic. Efforts to improve compliance with traffic regulations must consider these psychological aspects to be more effective.